An analysis of the optimal intrusion force of the maxillary central incisor with root horizontal resorption using the finite element method and curve fitting. Issue 13 (3rd October 2022) - Zhang, Xin; Li, Min-Qi; Guo, Jie; Yang, Heng-Wei; Yu, Jian; Li, Guo-Ju
Abstract: There are no studies on the optimal intrusion force in orthodontic patients with the existing root resorption (RR). The study aimed to analyze the optimal intrusion force for central incisors with existing horizontal root resorption using the finite element method (FEM). We calculated the optimal intrusion force using the finite element method and curve fitting. We found that with the increase of the maxillary central incisor's root horizontal resorption length, the optimal intrusion force interval's median gradually increases. If the resorption length is more significant than 1/2 of the root length, it is not recommended to use intrusion force theoretically.